THE IMPACT OF LEADERSHIP PATTERNS, INCENTIVE PROVISION, AND WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE AT INSTITUT ASIA MALANG - Risa Santoso (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2025)
This study investigates the influence of leadership patterns, incentive provisions, and the work environment on employee performance at Institut Asia Malang. A supportive work environment both socially and psychologically plays a vital role in fostering employee productivity. Moreover, effective leadership is instrumental in boosting motivation and loyalty among staff. A quantitative approach with descriptive and causal designs was adopted in this research, using random sampling to gather data from both academic and administrative employees. Multiple linear regression analysis was then employed to examine the relationships between these variables. The findings indicate that leadership patterns and the work environment have a significant effect on employee performance, with p-values of 0.045 and 0.035 respectively (p < 0.05). In contrast, incentive provision does not demonstrate a statistically significant impact (p = 0.541). Consequently, focusing on leadership development and creating an optimal work environment proves more effective in enhancing employee performance at Institut Asia Malang than relying on incentives alone.